Knowledge and Awareness on Prevention of Sexually Transmitted Diseases among Commercial Sex Workers - Haque, MR; Ghosh, K; Sultana, H; Saha, E; Kafi, A; Roy, P (TAJ: Journal of Teachers Association, 2018)
Objective: The main objective of the study was to assess the level of awareness on prevention and control of sexually transmitted diseases among 120 sex workers. Material and Methods: The cross-sectional study was conducted for one year. Data were collected through face to face interview using Bengali questionnaire. Data analysis was done using SPSS 17.0 software. Place and Period of Study: The study was conducted from January 1st to December 31st of 2014 among 120 sex workersliving in brothel of Daulodia,Rajbariin Bangladesh. Results: More than half (58.7%) of the respondents had children in the brothels. All the respondents (100%) heard about the sexually transmitted diseases. Majority (86.7%) of the respondents had knowledge on AIDS. Only a few (4.2%) respondents had knowledge on AIDS and Gonorrhea. Majority (91.7 %) of the respondents had knowledge on STD transmission from pregnant women. Almost all (97.5%, 98.3%)) of the respondents had the knowledge about STD transmissionnot from toilet or shaking hands respectively.Almost all of the (95.8%, 94.2%, 94.2%, 85.8% )respondents had the knowledge on STD transmission through sexual intercourse,injection,through mosquito,sharing same razor respectively. Most of them (81.7%) had good level of knowledge on STD transmission. Only above one tenth (11.7%) had moderate and poor level of knowledge.Almost all of them (96.7%, 95.9%, 95.9%) were found touse condom, agreed to keep one partner at a time,to reduce the number of sex partner respectively.Most of them (89.3%)did not knowthe HIV status of partner before sex,almost all (97.5%, 94.2% and 97.5%) agreed to avoid risky sex,to screen blood during transfusion, to avoid sharing needles & blade respectively. All (100%)of the respondents agreed for need of sexuality education for preventing STD.Almost all (98.30%)of the respondents had good awareness on Prevention and Control of Sexually Transmitted Diseases. There was no association between level of education and level of awareness (P> 0.005), between age and level of awareness (P> 0.005) and between duration of work and level of awareness (P> 0.005). Conclusion: Education is the most consistent and important determinant for prevention of STDs among all classes of people. TAJ 2016; 29(2): 47-56